2016
DOI: 10.1128/aem.03292-15
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Apis cerana Sacbrood virus Infection in Apis mellifera

Abstract: bSacbrood virus (SBV) is one of the most destructive viruses in the Asian honeybee Apis cerana but is much less destructive in Apis mellifera. In previous studies, SBV isolates infecting A. cerana (AcSBV) and SBV isolates infecting A. mellifera (AmSBV) were identified as different serotypes, suggesting a species barrier in SBV infection. In order to investigate this species isolation, we examined the presence of SBV infection in 318 A. mellifera colonies and 64 A. cerana colonies, and we identified the genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…In group I, although SXYL-2015, SXnor1–2012, and BJ-2012 were isolated from the Chinese honeybee A. cerana , those strains formed a closely related cluster with the strains originating overseas, such as AcSBV-IndK1A, AcSBV-IndII-2 (GenBank: JX270795), AmSBV-Australia (GenBank: KJ629183), AmSBV-Kor21, and SBV-UK. We deduced that SXYL-2015, SXnor1-2012, and BJ-2012 probably originated from SBV infecting Apis mellifera , and then infected A. cerana , indicating that SBV can cause interspecies infections, and these data are consistent with Gong’s results28. By contrast, HBQHD-2012, LNSZ-2011, GZ-2000, and GZ-2002 form a closely related cluster with groups II and III; this finding shows that these isolates originated from GZ-2000, which was first isolated from the Chinese honeybee A. cerana in Guangzhou in 2000.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In group I, although SXYL-2015, SXnor1–2012, and BJ-2012 were isolated from the Chinese honeybee A. cerana , those strains formed a closely related cluster with the strains originating overseas, such as AcSBV-IndK1A, AcSBV-IndII-2 (GenBank: JX270795), AmSBV-Australia (GenBank: KJ629183), AmSBV-Kor21, and SBV-UK. We deduced that SXYL-2015, SXnor1-2012, and BJ-2012 probably originated from SBV infecting Apis mellifera , and then infected A. cerana , indicating that SBV can cause interspecies infections, and these data are consistent with Gong’s results28. By contrast, HBQHD-2012, LNSZ-2011, GZ-2000, and GZ-2002 form a closely related cluster with groups II and III; this finding shows that these isolates originated from GZ-2000, which was first isolated from the Chinese honeybee A. cerana in Guangzhou in 2000.…”
Section: Discussionsupporting
confidence: 88%
“…Ma et al predicted and identified four major CSBV structural proteins by means of bioinformatics and mass spectrometry12. There are reported differences between CSBV and SBV in their physicochemical characteristics, pathogenicity, and immunogenicity131415; however, it is unknown whether these differences exist between CSBVs of different genotypes.…”
mentioning
confidence: 99%
“…Sacbrood virus (SBV) is a common virus belonging to the genus Iflavirus and causes failure to pupate and subsequent death in Apis mellifera [1][2][3]. It was the first identified iflavirus in European honey bees and a strain has evolved that also infects Asian honey bees, Apis cerana [4,5]. The A. cerana strain (Ac-SBV) shares more than 97% similarity with A. mellifera SBV isolates and causes more losses in A. cerana colonies than SBV in A. mellifera [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was the first identified iflavirus in European honey bees and a strain has evolved that also infects Asian honey bees, Apis cerana [4,5]. The A. cerana strain (Ac-SBV) shares more than 97% similarity with A. mellifera SBV isolates and causes more losses in A. cerana colonies than SBV in A. mellifera [4]. A. cerana is naturally resistant to Varroa mites and less prone to some common virus diseases found in A. mellifera; however, A. cerana apiaries in China were reporting serious losses caused by SBV [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, buttressing the health of managed pollinators must not be done at the expense of native pollinators, as honeybees can serve as reservoirs of diseases that threaten wild bees 201 203 and other managed bees 204 . More than 20,000 species of wild bees play critical roles in agriculture and native ecosystems, and disease risk is a threat to this critical component of biodiversity 10 , 186 .…”
Section: Applicationsmentioning
confidence: 99%